Preparation method of rapidly-formed Janus structure stretchable electrode

Through the Janus structure stretchable electrode preparation method, the Janus structure electrode with conductive and insulating surface separation is quickly formed by gravity-induced phase separation method, which solves the problem that stretchable electrodes in the prior art are difficult to achieve rapid preparation, high conductivity, stretchability and recyclability at the same time, and achieves an efficient and rapid preparation process and excellent electrode performance.

CN119724747APending Publication Date: 2025-03-28CHANGZHOU YIHONG TECHNOLOGY CO LTD
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411874498.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

It is difficult for existing stretchable electrodes to achieve rapid preparation, high conductivity, stretchability, low resistance variation and good recyclability at the same time, limiting their production efficiency and use benefits in practical applications.

Method used

Using the Janus structure, the Janus structure is used to prepare stretchable electrodes, and liquid metal particles are added to the solution system of thermoplastic polyurethane TPU and N,N-dimethylformamide DMF, and the Janus structure electrode is quickly formed by gravity-induced phase separation method to achieve separation of conductive and insulating surfaces.

Benefits of technology

Rapid molding (15 seconds), high conductivity (resistance <10 ohms), high tensile (250%), tensile strain insensitivity (<20%), excellent breathability, biosafety and recyclability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119724747A_ABST
    Figure CN119724747A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a rapidly-formed Janus structure stretchable electrode, an electrode material system is a material system composed of thermoplastic polyurethane (TPU), liquid metal particles and N, N-dimethylformamide (DMF), and electrode forming comprises two self-assembly processes. In the first self-assembly process, the liquid metal particles rapidly settle to form a Janus structure under the action of gravity; and a second self-assembly process: quickly dissolving DMF in water under the action of phase separation, and quickly separating out TPU to form a porous structure. The whole electrode forming process is about 15 seconds, which is the fastest stretchable electrode film forming process so far. The electrode has high conductivity, high stretchability and insensitivity to tensile strain, the electrode can spontaneously form a Janus structure with one conductive side and the other insulated side so as to achieve a self-protection structure for the whole electrode, and the electrode is expected to be applied to the flexible electronic fields of electronic skin, human body information detection, stretchable electronic devices and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of stretchable electrodes, and in particular relates to a method for preparing a rapid-prototyping Janus structure stretchable electrode. Background Art

[0002] Electronic skin is an emerging and rapidly developing electronic technology that provides a solid technical foundation for breakthroughs in soft robotics, personal healthcare, human-computer interaction, and medical electronics. Among them, electrodes are essential in the composition to maintain their device functions, including resistance, capacitance, piezoelectric, triboelectric types, etc. New technical requirements drive the transformation of flexible electrodes to stretchable electrodes to cope with more diverse and complex application scenarios. Conductivity and stretchability are considered to be the basic criteria for stretchable electrodes. At the same time, the stability of resistance under stretching is another important criterion for evaluating the performance of stretchable electrodes. The resistance of stretchable electrodes should remain almost constant within the required strain range to avoid interference with the sensing signal caused by changes in the conductivity of the stretchable electrode. In addition to the basic performance, the rapid and efficient preparation, long-term stability, and recyclability of stretchable electrodes are also advantageous in the context of a wide range of applications such as transient and green electronics. Although a large number of studies have focused on the development of stretchable electrodes, they can usually only achieve one or several of the above-mentioned desired characteristics. Simultaneously achieving a simple preparation process, rapid film formation, high conductivity and stretchability, low resistance change during stretching, and good recyclability for stretchable electrodes remains a huge challenge, which severely limits their production efficiency and use benefits in practical applications.

[0003] Flexible devices with Janus structures exhibit different properties on different surfaces, which helps solve the stability problem caused by stress mismatch. The Janus structure stretchable electrode designed by the present invention can be quickly formed (15 seconds) using a gravity-induced phase separation method. During the preparation process, two physical processes are involved, namely the precipitation of high-density LMs under gravity to form a Janus structure, and a phase separation process that assists in the rapid formation of a stable film. One side of the stretchable electrode is insulating TPU, while the other side is mainly liquid metal particles. The JSS film has excellent stretchability and conductivity, while maintaining high conductivity under complex operating modes such as stretching, folding and rotation. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a rapid prototyping Janus structure stretchable electrode to meet the requirements of flexible electronics under complex environmental changes.

[0005] The method for preparing a stretchable electrode of the present invention comprises the following steps:

[0006] Thermoplastic polyurethane TPU is used as a solute and N,N-dimethylformamide DMF is used as a solvent. The thermoplastic polyurethane TPU is dissolved in N,N-dimethylformamide DMF to form an original solution system; liquid metal particles are added into the original solution system to form a uniform suspension; the liquid metal particles settle under the action of gravity; during the settling process, deionized water is added into the suspension, the deionized water serves as a rapid prototyping initiator, N,N-dimethylformamide DMF is dissolved in water, and the thermoplastic polyurethane TPU is precipitated to form a porous structure.

[0007] Furthermore, the electrode includes a conductive surface and an insulating surface; the surface where the liquid metal particles settle is the conductive surface; a Janus structure is formed with one side conductive and the other side insulating; the opposite side of the conductive surface is the insulating surface, and there are no liquid metal particles in the insulating surface.

[0008] Furthermore, the mass ratio of TPU and DMF to form the original solution system is (0.8-1.5):10.

[0009] Furthermore, the liquid metal particles include Ga and In, and the mass ratios of Ga and In are 75% and 25% respectively.

[0010] Furthermore, the conductive surface resistance is less than 10 ohms, and the insulating surface resistance is greater than 1G ohms.

[0011] Furthermore, the stretchable range of the electrode is not less than 250%.

[0012] Furthermore, the suspension is divided into n sedimentation layers S1, S2, S3...S from top to bottom. n , the sedimentation layer is parallel to the horizontal plane;

[0013] During the sedimentation process of the liquid metal particles, for any sedimentation layer x, the mass flow conservation equation is:

[0014]

[0015] ρ is the density of the liquid metal particles, A x is the cross-sectional area of ​​the sedimentation layer, where x∈(1,n), represents the particle concentration in the sedimentation layer x, and z represents the differential quantity perpendicular to the carrier film.

[0016] Beneficial effects: Compared with the prior art, the present invention has the following significant features:

[0017] 1. A rapid prototyping method for preparing a Janus structure stretchable electrode is proposed. The electrode molding time is about 15 seconds, which is faster than the molding time of any Janus structure stretchable electrode to date.

[0018] 2. The Janus structure stretchable electrode has high conductivity (resistance <10 ohms), high stretchability (250%), and insensitivity to tensile strain (<20%); the Janus structure can achieve a self-protection structure for the entire electrode.

[0019] 3. The prepared Janus structure stretchable electrode has excellent gas permeability, biosafety and recyclability. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 It is a schematic diagram of the structure of the Janus structure stretchable electrode;

[0021] Figure 2 This is a physical picture of the conductivity difference test on both sides of the Janus structure stretchable electrode;

[0022] Figure 3 This is a SEM photo of the porous structure of the Janus structure stretchable electrode;

[0023] Figure 4 It is the tensile performance test of the Janus structure stretchable electrode;

[0024] Figure 5 It is the stretch insensitivity test of Janus structure stretchable electrode;

[0025] Figure 6 It is the permeability test of the Janus structure stretchable electrode;

[0026] Figure 7 It is the cytotoxicity test of Janus structure stretchable electrode;

[0027] Figure 8 is the recyclability of Janus structure stretchable electrodes. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.

[0029] The present invention provides a method for preparing a rapid prototyping Janus structure stretchable electrode, comprising the following steps:

[0030] The precursor solution is prepared, including thermoplastic polyurethane TPU as a solute and N,N-dimethylformamide DMF as a solvent, and the mass ratio of TPU to DMF is about (0.8-1.5):10; the thermoplastic polyurethane TPU is dissolved in N,N-dimethylformamide DMF to form a solution, liquid metal particles (75% Ga and 25% In) are added to the solution, and ultrasonic dispersion is performed for about five minutes to form a uniform suspension, and the suspension is dripped onto a carrier sheet with a length and width of 76*26 mm, respectively, and the liquid metal particles are rapidly settled under the action of gravity; during the rapid settling of the liquid metal particles, deionized water is added to the suspension, and N,N-dimethylformamide DMF is rapidly dissolved in water under the action of phase separation, and the thermoplastic polyurethane TPU is rapidly precipitated to form a porous structure, so as to obtain the stretchable electrode of the present invention, such as Figure 1 As shown; the pore diameter of the porous structure is 5-20 microns, such as Figure 3 Shown is the SEM photograph of the porous structure.

[0031] The rapid prototyping of the electrode of the present invention includes two self-assembly processes. In the first self-assembly process, liquid metal particles quickly settle under the action of gravity to form a Janus structure. In the second self-assembly process, N,N-dimethylformamide DMF quickly dissolves in water under the action of phase separation, and thermoplastic polyurethane TPU quickly precipitates to form a porous structure.

[0032] The surface where the liquid metal particles settle is the conductive surface of the electrode of the present invention, and the other surface is the insulating surface of the electrode of the present invention, forming a stretchable electrode with a specific Janus structure. The conductive surface has high conductivity (resistance <10 ohms), and the insulating surface has high resistance (resistance >1G ohms). In this specific embodiment, the mass ratio of TPU and DMF is about 1:10 to prepare the electrode, and the measurement is performed, such as Figure 2 As shown, the measured resistance of the conductive surface is 0.2 ohms, and the resistance of the insulating surface exceeds the measuring range.

[0033] The length, width and height of the Janus structure stretchable electrode are 76*26*0.5mm respectively, and the corresponding electrode forming time is about 15 seconds. The forming time of the electrode is related to the thickness. The thicker the thickness, the longer the forming time. The thickness of the stretchable electrode of the present invention is about 0.5mm, and the electrode at this thickness has the characteristics of high conductivity and high stretchability.

[0034] like Figure 4 As shown, the stretchable electrode of the Janus structure prepared by the present invention has high stretchability. The stretchable electrode of the Janus structure is cut into a 20*10 mm strip and fixed on a tensile machine to test its stretchability. The stretchable range can reach at least 250%.

[0035] like Figure 5As shown, the stretchable electrode with Janus structure prepared by the present invention is strain-insensitive. The stretchable electrode with Janus structure is cut into a 20*10mm strip and fixed on a tensile testing machine, repeatedly stretched by 200%, and the resistance change of the electrode is measured with a multimeter. The resistance change is less than 20% of the initial resistance, which proves that the electrode has the characteristic of strain insensitivity.

[0036] The Janus structure stretchable electrode prepared by the present invention has excellent air permeability, biosafety and recyclability. Figure 6 The air permeability test of the Janus structure stretchable electrode is about 4077.41 gm when the insulating surface and the conductive surface of the stretchable electrode of the present invention are facing upward. -2 day -1 The air permeability of the ordinary stretchable electrode was measured by turning the ordinary stretchable electrode with one side facing up and the other side facing up. The measured air permeability was about 260 g m -2 day -1 It can be seen that the air permeability of the electrode of the present invention is much higher than that of the ordinary stretchable electrode, which proves that the stretchable electrode of the present invention has excellent air permeability. Figure 7 As shown, it is a cytotoxicity test of the Janus structure stretchable electrode, and a blank control group, a negative control group, a positive control group and an experimental group are set up respectively. The blank control group is a cell culture solution, the negative control group is a commercial TPU film placed in the cell culture solution, the positive control group is a commercial TPU film immersed in a 20% DMOS solution for 20 minutes and then taken out and placed in the cell culture solution, and the experimental group is the stretchable electrode of the present invention placed in the cell culture solution. After three days of culture, the final cell survival rate of the experimental group is about 99.87%, proving that the stretchable electrode of the present invention has excellent biocompatibility. , such as Figure 8 As shown, the recyclability of the Janus structure stretchable electrode is that the stretchable electrode of the present invention can be dissolved again using DMF after being damaged. After undergoing the same preparation process, the stretchable electrode of the present invention can be recycled and reconstructed.

[0037] The prepared Janus structure stretchable electrodes can be used for physiological electrical signal detection, friction nanogenerators and strain resistor sensors.

[0038] Thermoplastic polyurethane TPU is dissolved in N,N-dimethylformamide DMF as the original solution system. The principle of the Janus structure stretchable electrode forming the Janus structure is: the liquid metal particles are in a suspended liquid state in the original solution system, and will slowly settle to the bottom over time. The density of the liquid metal particles is much higher than that of the solution system of TPU dissolved in DMF, which accelerates the deposition process. When the original solution system is dropped on a 76*26mm glass slide, the liquid metal particles will settle rapidly due to the height limit of the solution (about 0.5mm), gather at the bottom of the solution, and then form a Janus structure.

[0039] In order to facilitate analysis, the suspension with liquid metal particles is simplified into a two-dimensional plane, and the initial suspension is differentiated into n sedimentation layers S1, S2, S3…S n , each sedimentation layer is parallel to the carrier plate.

[0040] For any sedimentation layer x, the mass flow conservation equation is:

[0041]

[0042] ρ is the density of gallium-based liquid metal particles, A x is the cross-sectional area of ​​the sedimentation layer, where x∈(1,n), represents the particle concentration in the sedimentation layer x, and z represents the differential amount perpendicular to the carrier film;

[0043] is the mass of liquid metal particles in the sedimentation layer. inx and f outx represent the mass flow rates of liquid metal particles entering and leaving the sedimentation layer x, respectively.

[0044]

[0045] in, is the sedimentation rate of the liquid metal particles, is with Related functions.

[0046] For the top layer of the suspension where only liquid metal particles leave but no liquid metal particles enter, that is, the sedimentation layer S1, f in1 and f out1 They represent the mass flow rate of liquid metal particles entering and leaving the sedimentation layer S1, respectively, and are expressed as

[0047] The mass flow rate of liquid metal particles entering the sedimentation layer S1 is f in1 =0;

[0048] The mass flow rate of liquid metal particles leaving the sedimentation layer S1 is fout1 , expressed as:

[0049]

[0050] Where A1 represents the cross-sectional area of ​​the sedimentation layer S1, represents the particle concentration of liquid metal in the S1 layer;

[0051] For the case where only liquid metal particles enter but no liquid metal particles leave the top layer of the suspension, that is, the sedimentation layer S n ,

[0052] Leaving the sedimentation layer S n The mass flow rate of liquid metal particles f outn =0,

[0053] Entering the sedimentation layer S n The mass flow rate of liquid metal particles f inn , expressed as:

[0054]

[0055] The sedimentation process of liquid metal particles will cause the density of liquid metal particles in the upper layer to decrease and the density of liquid metal particles in the lower layer to increase. The concentration propagation velocity is obtained.

[0056]

[0057] is defined as the velocity vector of the liquid metal in the vertical direction. When f in >f out , the most obvious manifestation is S n When When f in <f out , the most obvious manifestation is S n The concentration propagation velocity value only describes the concentration change in a certain sedimentation layer and does not represent the actual movement direction of the liquid metal particles, because all liquid metal particles are only affected by gravity and their movement is inevitably downward at the macroscopic level.

[0058] There is a discontinuity between any two adjacent sedimentation layers. The concentration propagation velocity at the concentration discontinuity can be obtained from the Rankine-Hugoniot jump condition as follows

[0059]

[0060] in, and Represents S in adjacent layers x Lower surface layer and S x-1 The density of liquid metal particles in the upper surface layer. Since liquid metal particles tend to settle under the action of gravity, the distance between any adjacent layers

[0061]

[0062] is a dependency The functional relationship of represents the particle concentration of liquid metal, so:

[0063]

[0064] according to The definition of Therefore, Δv>0, that is, there is always a relationship between any two adjacent sedimentation layers, the equation is:

[0065]

[0066] Therefore, in an ideal state, the density of the metal particles in the suspension will show a certain gradient. Over time, the liquid metal particles at the top will accumulate downward, and the denser liquid metal particles will settle at the bottom, thus realizing a stretchable electrode with a Janus structure that is conductive at the bottom and insulating at the top.

[0067] The principle of rapid prototyping of the Janus structure stretchable electrode is that the DMF in the original solution system is easily soluble in water. When deionized water is used as an initiator, the deionized water enters the original solution system, and the DMF in the original solution system quickly dissolves in water, resulting in large and small pores in the middle of the electrode. The TPU quickly precipitates into a film due to the loss of solvent, thereby achieving rapid prototyping. The length, width and height of the electrode prepared by the present invention are 76*26*0.5mm, respectively, and the corresponding prototyping time is about 15 seconds. The prepared Janus structure stretchable electrode can be used for physiological electrical signal detection, friction nanogenerators and strain resistance sensors; electrodes of this size almost meet all application scenarios of stretchable electrodes in electronic skin, human body information detection and other aspects.

Claims

1. A method for preparing a stretchable electrode, characterized in that: Follow these steps: Thermoplastic polyurethane TPU is used as solute and N,N-dimethylformamide DMF is used as solvent, and the thermoplastic polyurethane TPU is dissolved in N,N-dimethylformamide DMF to form an original solution system; Adding liquid metal particles into the original solution system to form a uniform suspension; Liquid metal particles settle under the action of gravity; During the sedimentation process, deionized water is added to the suspension, N,N-dimethylformamide DMF is dissolved in water, and thermoplastic polyurethane TPU is precipitated to form a porous structure.

2. The method for preparing a stretchable electrode according to claim 1, characterized in that: The electrode comprises a conductive surface and an insulating surface; The surface onto which the liquid metal particles settle is a conductive surface; The opposite side of the conductive surface is an insulating surface.

3. The method for preparing a stretchable electrode according to claim 1, characterized in that: The mass ratio of TPU and DMF forming the original solution system is (0.8-1.5):

10.

4. The method for preparing a stretchable electrode according to claim 1, characterized in that: The liquid metal particles include Ga and In, and the mass ratios of Ga and In are 75% and 25% respectively.

5. The method for preparing a stretchable electrode according to claim 2, characterized in that: The conductive surface resistance is less than 10 ohms, and the insulating surface resistance is greater than 1G ohms.

6. The method for preparing a stretchable electrode according to claim 2, characterized in that: The stretchable range of the electrode is not less than 250%.

7. The method for preparing a stretchable electrode according to claim 1, characterized in that: The suspension is divided into n sedimentation layers S1, S2, S3...S from top to bottom. n , the sedimentation layer is parallel to the horizontal plane; During the sedimentation process of the liquid metal particles, for any sedimentation layer x, the mass flow conservation equation is: ρ is the density of the liquid metal particles, A x is the cross-sectional area of ​​the sedimentation layer, where x∈(1,n), represents the particle concentration in the sedimentation layer x, z represents the differential value perpendicular to the carrier film, and f inx represents the mass flow rate of liquid metal particles entering the sedimentation layer x, f outx represents the mass flow rate of liquid metal particles leaving the sedimentation layer x.

Citation Information

Cited By

  • Liquid metal-aerogel composite material with Janus structure as well as preparation method and application of liquid metal-aerogel composite material

    CN120748812A

  • Liquid metal-aerogel composite with Janus structure and preparation method and application thereof

    CN120748812B

  • Stretchable conductive polymer composite electrode, preparation method, regeneration method and application

    CN121096716A

  • Porous epidermal electrode based on liquid metal and preparation method of porous epidermal electrode

    CN121606297A